Contribution of self‐compassion to positive mental health among Korean university students. (11th September 2018) - Shin, Na Young; Lim, Young‐Jin
Abstract : Although evidence suggests self‐compassion can serve as an important predictor of positive mental health, few studies have examined the contribution of self‐compassion to mental health. This study examined the relations between six components of self‐compassion and three dimensions of positive mental health (Psychological, Emotional and Social Well‐being) in young Korean adults. A sample of 689 Korean college students were administered the Self‐Compassion Scale (SCS) and the Mental Health Continuum Short Form (MHC‐SF) to evaluate self‐compassion and positive mental health. A multiple indicators multiple causes (MIMIC) analysis revealed that Self‐Kindness significantly predicted all dimensions of positive mental health. Additionally, Over‐Identification significantly contributed to Emotional Well‐being, Common Humanity to Social Well‐being and Isolation to Psychological Well‐being. These results suggest Self‐Kindness is a key predictor of positive mental health and that specific components of self‐compassion are strongly related to specific dimensions of mental health in Koreans.